The Potential of Virtual Reality (VR) and Augmented Reality (AR) in Promoting Sustainable Education and Enhancing Public Awareness - Ruixu, Dong; Lianhua, Dong (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
This paper explores the transformative potential of Virtual Reality (VR) and Augmented Reality (AR) in advancing sustainable education and heightening public awareness of critical environmental issues. As the global community grapples with the urgent need to achieve the United Nations Sustainable Development Goals (SDGs), innovative educational tools are paramount. VR and AR technologies offer immersive, interactive, and engaging learning experiences that can significantly enhance the understanding and retention of complex sustainability concepts. This paper synthesizes existing research to examine the effectiveness of these immersive technologies in various educational contexts, from formal classroom settings to public awareness campaigns. We review several case studies that demonstrate the power of VR and AR to foster pro-environmental attitudes, promote behavioral change, and increase engagement with sustainability topics such as climate change, biodiversity loss, and resource conservation. The analysis reveals that by creating a sense of presence and emotional connection, VR and AR can bridge the psychological distance to environmental problems, making them more tangible and relatable. Furthermore, the paper discusses the alignment of these technologies with SDG 4 (Quality Education) and their contributions to other SDGs by fostering a generation of environmentally conscious and responsible citizens. Finally, we identify the current challenges, including accessibility, cost, and the need for standardized pedagogical frameworks, and propose future research directions to fully harness the potential of VR and AR for a sustainable future. The findings suggest that the strategic integration of immersive technologies into educational strategies can be a powerful catalyst for achieving global sustainability targets.